Genetic landscape of colorectal cancer patients manifesting tumor shrinkage during SARS-Cov-2 infection. (December 2022) - Ottaiano, Alessandro; Santorsola, Mariachiara; Circelli, Luisa; Cascella, Marco; Petrillo, Nadia; Perri, Francesco; Casillo, Marika; Granata, Vincenza; Ianniello, Monica; Izzo, Francesco; Picone, Carmine; Correra, Marco; et al.
We previously described three patients affected by metastatic colorectal cancer (mCRC) who experienced spontaneous tumour shrinkage during severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Thereafter, the patients were closely monitored and no systemic treatments were applied. Here, we report follow-up clinical information about these patients as well as genetic characterization of their primary tumours through the TruSigt™Oncology 500 Next Generation Sequencing test targeting 523 cancer-relevant genes. An Illumina NovaSeq 6000 platform was used to perform sequencing. Time-to-progression was 23 and 2 months, respectively, in Patients 2 and 3 while it was not reached in Patient 1. Patients 1 and 2 had the greatest anti-SARS-CoV-2 IgG titres. Assessment of genetic landscapes evidenced common mutation in BARD1 gene (p.Val507Met) in Patients 1 and 2. Although our report is descriptive in its nature, we suggest that complex and unexplored interactions between genetic background and components of the immune response to SARS-CoV-2 infection could be responsible of unexpected rare mCRC shrinkage.